UPAYA PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE DISKUSI TERBIMBING DI SDN 001 SUNGAI SALAK - Susi Hariani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the students’ learning outcomes on social science learning subjects through the guided discussion learning method. The guided discussion method can be used to achieve dexterity, accuracy, opportunity, and skills with the process of providing continuous and systematic support for students to solve the problems they faced in order to achieve the skills to be able to understand themselves. The research used was a Classroom Action Research (CAR) byusing a research design model of Kemmis and Mc. Taggart. The research was conducted at SDN Sungai Salak. The population of the research involved 19 students of class V. The research used quantitative data analysis. Descriptive statistical data collection techniques were observations, interviews, and evaluation tests. Based on the results, students’ learning outcomes obtained by applying the guided discussion method were increasingly improved. At the end of the first cycle, the group work scores obtained by groups I-IV were 75, 80, 85, and 85. In addition, the average score of students’ learning outcomes obtained was 75.26 reaching classical completeness at 68.42%. In cycle II, the results obtained by students based on group work scores and individual learning outcomes at the end of the cycle were 90, 100, 100, and 95. While the average score of students’ learning outcomes obtained was 83.15 reaching classical completeness at 89.47%.